Ayat-Ayat Tentang Dakwah Nabi Muhammad SAW dalam Alqur’an: Aktualisasi dan Ideologi yang Berusaha Ditanamkan - Ilma Amalia; Fitriyani Fitriyani; Nissa Nurbayti (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
This article discusses one of the procedures of the Prophet Muhammad in developing the Islamic religion or what is usually called Da'wah. Knowledge about this da'wah can lead humans to become people who invite society toward the Creator. The number of people who want to show the true path of Islam alienates people from it, this cannot be separated from their level of understanding of the Prophet's preaching of Islam. The purpose of this article is to reveal the verses of the Qur'an about the preaching of the Prophet Muhammad SAW, how it is actualized today, and what ideology these verses want to instill. The research method applied by the author in this paper is a qualitative method with a descriptive approach. The results obtained by the author from the research that has been carried out are that there is an actualization of the Prophet Muhammad's preaching which leads to the preaching of love or preaching with a loving approach and the ideology of preaching that is attempted to be instilled in these preaching verses is the ideology of preaching.